KOMUNIKASI REMAJA DENGAN AYAH MASIH MINIM: STUDI PADA SISWA SMA DI KOTA BOGOR - Firdanianty, Firdanianty; Lubis, Djuara Pangihuta; Puspitawati, Herien; Susanto, Djoko (Jurnal Ilmu Keluarga dan Konsumen, 2016)
Family communication is needed to build a strong bonding between the adolescents and their parents. This study aimed to analyze the relationship of characteristics of the adolescent and family to adolescent’s communication patterns with father and mother. Respondents were grade of 2nd high school students in Bogor City as many as 372 students aged 15-18 years old. Communication patterns were measured by five dimensions that are the topic, duration, frequency, media, and situation of communication. Data were analyzed by independent sample t-test and Pearson correlation. The results showed that there were differences in communication between boys and girls with their father and mother. Adolescents were more open and more often communicate with mother than father, both boys and girls. Other findings showed a significant negative correlation between the age of the fathers and the topic of conversation of adolescents-fathers (r=-0,126, p=0,015). In addition, there was a very significant negative correlation between birth order of adolescent with the topic of conversation of adolescents-mothers (r=-0,174, p=0,001) and communication media (r=-0,140, p=0,007). Similarly, the age of the mother and the topic of adolescents-mothers were very significant negative correlation (r=0,135, p=0,009). These findings revealed limited communication between father and his adolescent